Incidence of ablation‐induced esophageal lesions and gastroparesis in patients undergoing ablation index guided high power short duration atrial fibrillation ablation. (9th November 2022) - List, Stephan; Meinhardt, Christian; Mueller, Julian; Deneke, Thomas; Barth, Sebastian; Waechter, Christian; Luesebrink, Ulrich; Elsaesser, Albrecht; Arlt, Alexander; Halbfass, Philipp
Abstract: Introduction: Aim of this study was to evaluate the incidence of ablation‐induced endoscopically detected esophageal lesions (EDEL) and gastroparesis in patients undergoing high‐power short‐duration (HPSD) atrial fibrillation (AF) ablation using different target ablation index (AI) values. Methods and Results: Consecutive patients undergoing AF ablation were included. Radiofrequency (RF) ablation was performed using HPSD ablation (50 W, target AI of 320 and 350 (group 1) and 380 (group 2) at posterior wall). Postablation endoscopy was performed in all patients. In total, 233 patients (66.8 ± 10 years; 52% male) were included consecutively ( n = 137 patients in group 1 and n = 96 patients in group 2). Mean AI values und RF time at posterior wall was significantly higher and longer in group 2 compared to group 1 patients (413 ± 9 vs. 392 ± 19 AI, p < 0.01; 9.0 ± 0.8 s vs. 7.8 ± 0.7 s, p < 0.01). Esophageal endoscopy revealed esophageal lesions or gastroparesis in 43 of 233 patients (18.5%) in the total cohort (13.1% in group 1 and 26.0% in group 2; p = 0.02). Incidence of EDEL was 8.0% and 13.5% in group 1 and group 2, respectively. According to logistic analysis incidence of EDEL and/or gastroparesis was significantly lower in patients with a higher body mass index and higher in group 2 patients compared to group 1 patients. Conclusion: The incidence of EDEL or gastroparesis in patients undergoing HPSD AF ablation was 18.5% in the total cohort. The risk of EDEL and gastroparesis was associated with a higher AI target value of 380 compared to 320 and 350 at posterior wall and was reversely associated with body mass index.